2020
DOI: 10.5194/hess-24-115-2020
|View full text |Cite
|
Sign up to set email alerts
|

Stream temperature and discharge evolution in Switzerland over the last 50 years: annual and seasonal behaviour

Abstract: Abstract. Stream temperature and discharge are key hydrological variables for ecosystem and water resource management and are particularly sensitive to climate warming. Despite the wealth of meteorological and hydrological data, few studies have quantified observed stream temperature trends in the Alps. This study presents a detailed analysis of stream temperature and discharge in 52 catchments in Switzerland, a country covering a wide range of alpine and lowland hydrological regimes. The influence of discharg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 59 publications
(108 reference statements)
20
64
1
Order By: Relevance
“…The averaged warming rate of studied streams during the last years (0.25°C per year, 80% CI 0.19–0.32°C) is considerably higher than that of local air temperature and the recently observed and modelled warming of Swiss streams in alpine settings (Michel, Brauchli, Lehning, Schaefli, & Huwald, 2020). This long‐term survey over 40 years revealed an average slope of +0.33°C per decade for Swiss streams with diverse catchment topography, elevation and size.…”
Section: Discussionmentioning
confidence: 57%
“…The averaged warming rate of studied streams during the last years (0.25°C per year, 80% CI 0.19–0.32°C) is considerably higher than that of local air temperature and the recently observed and modelled warming of Swiss streams in alpine settings (Michel, Brauchli, Lehning, Schaefli, & Huwald, 2020). This long‐term survey over 40 years revealed an average slope of +0.33°C per decade for Swiss streams with diverse catchment topography, elevation and size.…”
Section: Discussionmentioning
confidence: 57%
“…Michel et al. (2020), for example, found that between 1999 and 2018 the annual discharge of the Emme already decreased each decade by 12% ± 4%. Additionally, Addor et al.…”
Section: Methodsmentioning
confidence: 99%
“…The future impact of PKD on brown trout, grayling, and salmon populations is greatly dependent on how water temperature, precipitation, and evaporation change in the context of the climate crisis (Borgwardt et al., 2020; Masson‐Delmotte et al., 2018). Water temperatures in central Europe have already increased by 1–2°C (Daufresne & Boët, 2007; Kędra, 2020; Michel et al., 2020; Webb & Nobilis, 2007) and patterns of precipitation have changed in quality (increasingly torrential rain, less snow) and seasonality (decreases in summer, increases in winter) (Masson‐Delmotte et al., 2018). Under these conditions, salmonids are estimated to have already lost half of their population density (Arndt et al., 2019; Burkhardt‐Holm & Zehnder, 2018; Waldner et al., 2020).…”
Section: Discussionmentioning
confidence: 99%